Potential Protective Effect of Dengue NS1 Human Monoclonal Antibodies against Dengue and Zika Virus Infections - Rochanawan Sootichote; Wilarat Puangmanee; Surachet Benjathummarak; Siriporn Kowaboot; Atsushi Yamanaka; Korbporn Boonnak; Sumate Ampawong; Supawat Chatchen; Pongrama Ramasoota; Pannamthip Pitaksajjakul (Biomedicines, 2023)
Due to the lack of an effective therapeutic treatment to flavivirus, dengue virus (DENV) nonstructural protein 1 (NS1) has been considered to develop a vaccine owing to its lack of a role in antibody-dependent enhancement (ADE). However, both NS1 and its antibody have shown cross-reactivity to host molecules and have stimulated anti-DENV NS1 antibody-mediated endothelial damage and platelet dysfunction. To overcome the pathogenic events and reactogenicity, human monoclonal antibodies (HuMAbs) against DENV NS1 were generated from DENV-infected patients. Herein, the four DENV NS1-specific HuMAbs revealed the therapeutic effects in viral neutralization, reduction of viral replication, and enhancement of cell cytolysis of DENV and zika virus (ZIKV) via complement pathway. Furthermore, we demonstrate that DENV and ZIKV NS1 trigger endothelial dysfunction, leading to vascular permeability in vitro. Nevertheless, the pathogenic effects from NS1 were impeded by 2 HuMAbs (D25-4D4C3 and D25-2B11E7) and also protected the massive cytokines stimulation (interleukin [IL-]-1b, IL-1ra, IL-2, IL-4, IL-5, IL-6, IL-8, IL-9, IL-13, IL-17, eotaxin, granulocyte colony-stimulating factor, granulocyte-macrophage colony-stimulating factor, Inducible protein-10, monocyte chemoattractant protein-1, macrophage inflammatory protein [MIP]-1 α, MIP-1β, tumor necrosis factor-α, platelet-derived growth factor, and RANTES). Collectively, our findings suggest that the novel protective NS1 monoclonal antibodies generated from humans has multiple therapeutic benefits against DENV and ZIKV infections.